Gastric cancer simultaneously complicated with extrahepatic bile duct metastasis and portal vein tumor thrombus: a case report - Naohiko Otsuka; Yasuhiko Nakagawa; Hiroshi Uchinami; Yuzo Yamamoto; Junichi Arita (Surgical Case Reports, 2023)
Abstract Background Gastric cancer metastatic to the extrahepatic bile duct or accompanied by portal vein tumor thrombus (PVTT) is rare. To our knowledge, there have been no cases complicated with both of these factors. Case presentation A 72-year-old man presented with icterus and melena. A biochemical blood test showed abnormal values for hepatobiliary enzymes and a tumor marker, and abdominal computed tomography scan revealed wall thickening of the lower bile duct with intra- and extra-hepatic bile duct dilatation and PVTT. A biopsy of the lower bile duct during endoscopic retrograde cholangiopancreatography demonstrated a moderately differentiated tubular adenocarcinoma. Moreover, gastroduodenoscopy showed a type 3 tumor at the lesser curvature of the gastric antrum, and an endoscopic biopsy demonstrated a moderately differentiated tubular adenocarcinoma. We diagnosed concomitant gastric cancer and distal bile duct accompanied by PVTT, and pancreatoduodenectomy with combined resection of the portal vein was performed. The resected specimen revealed a tumor in the lesser curvature of the gastric antrum and circumferential wall thickening in the lower bile duct. In pathological findings, infiltration of a moderately differentiated tubular adenocarcinoma from the mucosal layer to the subserosal layer of the stomach was observed. In contrast, a moderately differentiated tubular adenocarcinoma demonstrating the same histological type as the gastric cancer had spread not to the mucosal layer but mainly to the fibromuscular layer of the lower bile duct. Immunohistochemical staining showed identical patterns between gastric cancer and the bile duct tumor: negativity for cytokeratin 7 (CK7), and positivity for CK19 and 20. Therefore, the final diagnosis was extrahepatic bile duct metastasis from gastric cancer with PVTT. Unfortunately, multiple liver metastases occurred in the early postoperative period and chemotherapy was conducted, but the patient died 12 months after the surgery. Conclusions In the diagnosis of extrahepatic bile duct metastasis, immunohistochemical staining of gastric cancer and the bile duct tumor was essential and helpful as decisive evidence.